Pengabdian Diversifikasi Olahan Ikan Slengek - Prasetya, Andwini; Nurmalia, Ana; Yumiati, Yossie; Afriani, Ririn; Purnamasari, Resta (Jurnal Dehasen Mengabdi, 2024)
Kawasan Kota Tuo is one of the coastal areas in Bengkulu City. Most of the livelihoods of the residents of Kawasan Kota Tuo are fishermen. One of the fish that many fishermen get from Tuo City is slengek fish. Slengek fish is a typical fish from the Bengkulu region which is usually obtained in large quantities. However, this fish has a fairly cheap price, which is around Rp. 5000, -/Kg. So it is necessary to have information and processing technology that can add added value and shelf life. Therefore, training and counseling were held on the processing of dimsum and nuggets made from slengek fish. After the service was carried out in Kawasan Kota Tuo, the community had obtained information and knowledge about the technology for processing slengek fish into products that have added value, namely dimsum and nuggets and the community had received digital marketing counseling that had never been received before and through this training partners were guided how to use social media as a forum for the promotion of its products so that it is expected to be a stimulant of economic growth.